In Vitro Analysis of Antibacterial Activities of Curry Leaf (Murraya koenigii) Extract Towards Bacteria Edwardsiella tarda - Arif Syaifurrisal; Arief Prajitno; Mohamad Fadjar; Farid Mukhtar Riyadi; Annisa Isti Fauziyyah (Journal of Aquaculture and Fish Health, 2021)
This study analyzed the antibacterial activity of curry leaf extract (Murraya koenigii) on the growth of Edwardsiella tarda bacteria. This study aims to determine the bioactivity and antibacterial effectiveness of M. koenigii leaf extract against the growth of E.tarda bacteria. Inhibition test was carried out by delusion (MIC test) and diffusion (disc test) methods. MIC test used 5 variations of concentration: 1 mg/L, 10 mg/L, 100 mg/L, 500 mg/L and 1,000 mg/L on TSB (Tryptone Soya Broth) media; it was incubated for 24 hours. While the disc test used 5 variations of concentration: 100 mg/L, 200 mg/L, 300 mg/L, 400 mg/L and 500 mg/L on TSA (Tryptone Soya Agar) media and incubated for 2x24 hours. Chloramphenicol (5 mg/L)  was used as a positive control, and distilled water was used as a negative control.                    M. koenigii leaf extract contains natural bioactive; it was bacteriostatic antibacterial due to bacteria's growth after 48 hours incubation. The highest inhibition diameter of E.tarda was 7,20 mm at a concentration of 500 mg/L after 24 hours incubation. The highest inhibitory effectiveness was at a concentration of 500 mg/L with effectivity 56.3%, while it declined to 46,44% after 48 hours incubation.